GAMBARAN KEPUASAN PASIEN TERHADAP PELAYANAN DI INSTALASI GAWAT DARURAT RSUD CILILIN - Feti Syaptiah; Lidwina Triastuti Listianingsih; Florentina Dian Maharina (Jurnal Kesehatan, 2022)
The provision of services in order to provide patient satisfaction in particular. Emergency services can be assessed from the ability of nurses in terms of reliability, speed responsiveness, assurance, empathy, and appearance of the nurse to the patient. This study aims to determine description of patient satisfaction with services at the Emergency installation at Cililin Hospital, West Bandung Regency in 2021. The research method used is descriptive quantitative research, with cross sectional approach to 127 respondents using a questionnaire. The results showed that 4.32% of respondents stated that they were very dissatisfied, 1.92% dissatisfied, and 8.52% stated less satisfied with the service. Flat-the average value of patient satisfaction is in the category of being satisfied with the emergency services of the Cililin Hospital.   Keywords: patient satisfaction, emergency services